A Review Paper on Operational Research (International Journal of Innovative Research in Computer Science & Technology, 2020)
Any action poses ethical issues, questions  about "good" and "right" ways of doing and living; or  questions about beliefs and obligations to place them  differently. Operational study (OR) has since its inception  been interested in these issues, including professional  conduct, differential handling of the OR, the social  position of the OR, the OR action mechanism and the  contents of the OR study. This has culminated in the  advancement of research approaches and systems to help  clients explore the ethical dimension of their decisions. The analysis identifies a variety of significant, well established and vigorous research projects, and extends  research findings to a wide range of core issues. The main  governmental and commercial concerns of the day are  and sustainability. They are also at the very heart of daily  OR's more global choices. 'Ethics' thereby offers OR with  a valuable emphasis on both building knowledge and  offering research subjects for those involved. Any study  topics are proposed as a result of the analysis.
Keywords: Decision Making; Ethical Concerns; Ethical Issues; Operational Research